Music and sedation relieve intraoperative stress: A randomized controlled trial - Kaoru Yamashita; Toshiro Kibe; Akari Uto; Shusei Yoshimine; Minako Uchino; Mitsutaka Sugimura (PLoS ONE, 2025)
Music is useful for relieving anxiety; however, its impact on autonomic nervous system activity and circulatory dynamics during tooth extraction surgery under intravenous sedation is unclear. We conducted a prospective randomized controlled trial to compare the effects of music listening on circulatory dynamics and autonomic nervous system activity during the extraction of impacted mandibular third molars under intravenous sedation. We hypothesized that music listening combined with intravenous sedation would enhance stress reduction. In this randomized controlled trial, 34 women aged 20–40 years were assigned to a music or control group. Patients in the music group listened to music during tooth extraction under intravenous sedation. Autonomic nervous system activity, heart rate, and systolic blood pressure were assessed in both groups. Statistical significance was set at p < 0.05. Systolic blood pressure and autonomic nervous system activity were not significantly different between the two groups. However, the heart rate during the separation of the tooth crown, extraction, and suturing was significantly lower in the music group than in the control group (p < 0.05). Within-group systolic blood pressure comparisons showed significant differences during treatments between the groups. Intraoperative music listening may enhance the stress-reducing effects of intravenous sedation, as auditory intervention attenuates blood pressure variability and increments in heart rate even when the level of consciousness is reduced by sedation. The combination of intravenous sedation and music listening may be useful for reducing stress during dental treatment. Trial registration UMIN Clinical Trials Registry, UMIN 000054970